Fortification of EFB compost as a growing media for oil palm seedling / Nor Hidayah Abd Rahman - Abd Rahman, Nor Hidayah (Faculty of Plantation and Agrotechnology, 2018)
Nowadays, limited of the top soil resources was due to degradation by deforestation and urbanization for industrialization sector. Meanwhile, by using composted EFB as a component for growing media for oil palm seedlings show positive effect on growth performance oil palm seedlings and can manage properly waste from oil palm. This study was conducted to investigate the effect of fortification of EFB compost as a growing media on the growth performance at pre-nursery stage for oil palm seedlings. There were, four treatment with different of fortification of growing media, T0 (EFB compost 100%), T1 (EFB compost + gel), T2 (EFB compost + gel + CD + CIRP), T3, (EFB compost +gel + CD+ CIRP + DC). Growth performance of oil palm seedlings such as plant height, plant width, and leaves length was measured on weekly basis. Data on plant biomass and root length were measured at the end of this study. The data were analyzed using by One – Way ANOVA. Based on growth performance of oil palm seedlings, it was noticed that 100% EFB show better growth performance compared to other fortification of growing media. However, ANOVA show only parameter of leaves length and root length have significant differences with other treatment (P < 0.05). Most of growing media show suitable soil pH for plant growth. The fortification of these growing media were resulted to increase in pH, low salinity (below the optimum level) and the nutrient also were increased except for addition of decanter cake.